Holiness As Culmination of Yoga - Kadankavil, Thomas (Journal of Dharma, 1995)
The inter-relation between the ascetical disciple and holiness is a fact unmistakably found in all religious literature. The epithet 'His Holiness' (divya) referring to high dignitaries inthe world re- ligions unwittingly betrays an implicit philosophy that those who adopt ascetical methods of achieving liberation from the msof the world (samsara) will gradually attain higher .gradesof holinessand a consequent union (yoga) with the divine essencein proportion to their holiness. Approximation to the divine is the standardof measuring holiness. Thephilosophical world in generalandthe Indian thought in particular have spent, in the past, enormoustime and human speculative energy to give a detailedaccount of the progress of the imperfect to the fullness of perfection or reality which is also fullness of life and light (Br, Up. 1,3,28). Theself perception that the present condition of the self is not the ideal one is the motivating force for one to seekthe fullness of perfectionandunion with it. The mind-boggling metaphysicalissue in this connection is to settle on a satisfactory definition of the natureof this relation between the imperfect (the human soul, atman) and the perfect (the Reality, Brahman)